2020
DOI: 10.22435/jek.v19i2.2893
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Giardiasis Dan Kondisi Hygiene Perorangan Pada Murid Paud Di Kb-Tk Al Amin Paciran Lamongan

Abstract: ABSTRACT Small intestine infection caused by Giardia lamblia (giardiasis) occurs mostly in children living in developing country with poor sanitation. This study aims to determine the risk of giardiasis and personal hygiene conditions in pre-school students at KB-TK Al Amin Paciran Lamongan aged 2-6 years. Number of samples were 61 students, the dependent variable was the incidence of giardiasis, and independent variable was personal hygiene including nail hygiene, hand washing habit, footwear habit, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
2
2
1
Order By: Relevance
“…infection. The finding is in contrast to study conducted by (Nengsih et al, 2020) which stated the habit of defecating 5.73 times could increase the risk of Giardia spp. infection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…infection. The finding is in contrast to study conducted by (Nengsih et al, 2020) which stated the habit of defecating 5.73 times could increase the risk of Giardia spp. infection.…”
Section: Discussioncontrasting
confidence: 99%
“…is a common intestinal protozoan that infects humans, as well as animals and is considered a zoonotic disease. The highest incidence of cases was found in developing countries ranging from 20-30% compared to developed countries which rang from 3-7% (Nengsih et al, 2020). Giardiasis is transmitted by either direct or indirect mechanisms (Yaoyu Feng, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The research results also showed that there was no significant relationship between open defecation habits and the incidence of diarrhea in toddlers in Karangkamulyan, with a p-value of 0.505 (>0.05). However, this was not in line with previous research on the relationship between open defecation habits and the incidence of giardiasis, which found that children with open defecation habits had a 13.33 times higher risk of contracting giardiasis compared to those with good personal hygiene (14).…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with giardiasis can experience acute diarrhea or chronic diarrhea. The acute phase of giardiasis lasts 3-4 days and the chronic phase lasts two years or more, characterized by weight loss due to intermittent diarrhea, leading to malabsorption (14).…”
Section: Discussionmentioning
confidence: 99%
“…Temuan yang serupa dapat dilihat pada penelitian di Desa Mojo, Surabaya pada tahun 2018 (1,8%) serta di KB-TK Al Amin Paciran Lamongan, Jawa Timur pada tahun 2020 (8,2%). 19,20 Sementara itu, penelitian di Pesantren X di Surabaya pada tahun 2019 menunjukkan hasil yang bertentangan dimana prevalensi kasus infeksi Giardia lamblia mencapai angka 20%. 21 Penemuan kasus infeksi parasit usus Giardia lamblia menandakan bahwa masih terdapat faktor risiko yang berhubungan dengan parasit tersebut.…”
Section: Prevalensi Infeksi Parasit Usus Tunggal Giardia Lambliaunclassified